2018
DOI: 10.1111/jcmm.13609
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing amplification of late‐outgrowth endothelial cells by bilobalide

Abstract: Transfusion of autologous late‐outgrowth endothelial cells (OECs) is a promising treatment for restenosis after revascularization. Preparing cells by in vitro amplification is a key step to implement the therapy. This study aimed to demonstrate that bilobalide, a terpenoid, enhances the OEC amplification. Human‐, rabbit‐ and rat OECs and a mouse femoral artery injury model were used. Expanding OECs used endothelial growth medium‐2 as the standard culture medium while exploring the mechanisms used endothelial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Our previous results showed that external oxidative stress can also lead to HO • formation being tightly linked with the production of singlet oxygen in U937 cells (Rác et al, 2015). Since HPF has been identified to be a probe that can also react with other reactive species including but not limited to peroxynitrite, EPR spectroscopy was needed to validate our results (Dunand et al, 2007;Carlisi et al, 2014;Liu et al, 2018). When other methods are not available, an alternative fluorochrome (for instance, BODIPY) with higher sensitivity to HO • could be a potential candidate (Lei et al, 2017).…”
Section: Imaging Of Hydroxyl Radical Formation During Cell Differentimentioning
confidence: 65%
“…Our previous results showed that external oxidative stress can also lead to HO • formation being tightly linked with the production of singlet oxygen in U937 cells (Rác et al, 2015). Since HPF has been identified to be a probe that can also react with other reactive species including but not limited to peroxynitrite, EPR spectroscopy was needed to validate our results (Dunand et al, 2007;Carlisi et al, 2014;Liu et al, 2018). When other methods are not available, an alternative fluorochrome (for instance, BODIPY) with higher sensitivity to HO • could be a potential candidate (Lei et al, 2017).…”
Section: Imaging Of Hydroxyl Radical Formation During Cell Differentimentioning
confidence: 65%
“…Bilobalide (BB) is a sesquiterpenoid with 15 carbon skeletons and is initially found in Ginkgo biloba leaves (Liu et al, ). Ginkgo biloba leaves are largely applied in traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Transfusion of autologous late‐outgrowth endothelial cells (OECs) is a promising treatment for restenosis after revascularization. BB can increase nitric oxide (NO) production and prolong the lifespan of available NO to enhance the growth and in vitro expansion of OEC, which may simplify the preparation of OECs for the autologous‐OECs‐transfusion therapy (Liu et al, 2018). Besides, BB can increase the expressions of β‐catenin and enhance the secretion of vascular endothelial growth factors (Zhang et al, 2019).…”
Section: Pharmacological Effects Of Bbmentioning
confidence: 99%